ANALISIS MIKOFLORA DALAM MAKANAN FERMENTASI TRADISIONAL KEMPONG DI DESA KARANGPUCUNG KIDUL, LINGGAPURA BUMIAYU JAWA TENGAH - Devia Kusmawati Arfina; Endang Kusdiyantini; MG Isworo Rukmi (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Kempong is a traditional fermented foods which is traditionally made of palm kernel cake substrate from the South Karangpucung Linggapura Bumiayu village, Central Java. This study is aimed to identify a mold which has a role in the fermentation process and testing in an activity of Kempong’s enzyme from mycoflora obtained. Proximate analysis of the samples of mold and palm kernel cake are conducted to determine the nutrient content of the substrate and fermentation products. The Results isolation, from the environment, substrate, laru and product, show 14 isolates of molds, there are R.oryzae, A. niger Van Tieghem, A. carbonarius, Geotrichum candidum, A. ochraseus, Rhizomucor sp, A. chevalieri, A. tamarii, A. oryzae, A. flavus, A. nidulans, A. fumigatus, A. glaucus, and A. parasiticus. R. oryzae is a mold found in every material examined. It indicates that the fermentation is done mainly soothers by R. oryzae. Proximate analysis of the kempong, shows a levels of carbohydrate 16.67%, 74.03% water, 0.75% ash, 2.80% fat and 5.77% protein. Nutrients content except water are lower than the substrate palm kernel cake. Decreasing of protein, fat, and carbohydrate fermentation are caused by R. oryzae. Keywords: kempong, mycoflora, enzyme activity, proximate analysis.